Guidelines for quality assurance programmes for blood transfusion services (World Health Organization, 1993)
A comprehensive guide to each component of a quality assurance program for blood transfusion services, whether established in a small hospital blood bank or a large transfusion centre. Measures described are intended to ensure the maximum safety of all procedures for donors, recipients, and the staff themselves. Arguing that a system of quality assurance should be implemented in all transfusion services and blood banks, the book emphasizes the vital importance of strict quality control procedures at each stage of each procedure.